Design of L-band wideband high-gain circularly-polarized microstrip antenna for satellite communication system - Sui Tao; Xing Sirui; Sun Wei; An Xiangdong (Dianzi Jishu Yingyong, 2022)
In response to the requirements of satellite L-band communication and forwarding systems, a novel type of satellite-borne L-band broadband high-gain circularly polarized microstrip antenna is designed. The microstrip antenna adopts a side-fed feeding method as a whole, adopts an H-shaped slot coupling feeding method to achieve a wide frequency band, and uses a Wilkinson phase shift power splitter to achieve the phase difference between the two signals to meet the circular polarization, and add the antenna back reflector and foam layer between the boards to increase gain and stabilize the structure. Through the analysis of electromagnetic simulation software, it can be obtained that the gain is 8.3 dBi at the center frequency point of 1.45 GHz, the axial ratio is 0.7 dB, the relative bandwidth is 23.5% when the gain is greater than 7.5 dBi and the return loss is less than -10 dB. The actual measurement results of the antenna processing are basically consistent with the simulation results, which have certain guiding significance for the design of the L-band wireless communication system.